Pengalaman pemanfaatan cloud storage mahasiswa Teknik Komputer Universitas Diponegoro (Undip) dalam pengelolaan arsip digital - Sinta Wulandari; Roro Isyawati Permata Ganggi (Jurnal Informatio, 2021)
The use of cloud storage every student is certainly different, different behaviors also affect how individuals manage and use the digital archives they have stored in cloud storage. The purpose of this study is to find out how cloud storage behavior emerges when managing digital archives that students have in their educational activities. This study is done qualitatively with phenomenological methods through interviews to active computer engineering students Undip and observation as techniques in obtaining data. The data analysismethod used in this study is thematic analysis method, which is used to find patterns or themes by analyzing the data obtained then associated with the phenomenon found through the researchers' glasses. The results of this study obtained two themes, namely student knowledge regarding the management of digital archives owned using cloud storage and the behavior of using cloud storage that was raised by computer engineering students. While managing digital archives owned by students, it tends to be done simply in accordance with their knowledge and abilities. The management stage is carried out starting from the selection stage, the structuring and grouping stage, the evaluation stage and the meeting again. All stages of management that are carried out are of course related to one another. The utilization behavior shown by students has different goals in various ways to help with their lecture activities. The behavior of using cloud storage that is carried out is adjusted to the needs and interests of students to be able to meet information needs to support their academic activities.